SISTEM PAKAR DIAGNOSA KERUSAKAN KAMERA MENGGUNAKAN METODE DEMPSTER SHAFER - Ivan Santoso (CV. Multi Kreasi Media, 2024)
In this day and age, photography is very popular in Indonesia, many people want to document the moments of their activities with camera devices. Sometimes, the use of the camera that is arbitrary or does not follow the rules can cause damage to the camera. Lack of knowledge about cameras makes amateur users confused if there are problems that arise if there is damage and in the end the user decides to buy a new one because of the user's ignorance in repairing the camera. Camera experts or technicians are people who can check and repair cameras. However, limited expert readiness is not always available 24 hours, especially in locations far from settlements, it will be complicated to consult an expert or camera technician at an important time in the event of a camera malfunction. Therefore, the author makes an Expert System for Diagnosing Damage to the Camera using the Dempster Shafer Method. The method used is Dempster Shefer where this method focuses on the magnitude of the belief that a symptom of damage supports the diagnosis of certain damage. The expected results can help camera users diagnose camera malfunctions and their solutions.